1995
DOI: 10.1146/annurev.pc.46.100195.002421
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation: Measurements, Theory, and Atmospheric Applications

Abstract: New experiments have succeeded in measuring actual rates of nucleation and are revealing the shortcomings of classical nucleation theory, which assumes that the molecular-scale regions of the new phase may be treated using bulk thermodynamics and planar surface free energies. In response to these developments, new theories have been developed that incorporate information about molecular interactions in a more realistic fashion. This article reviews recent experimental and theoretical advances in the study of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
284
2
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(292 citation statements)
references
References 0 publications
3
284
2
3
Order By: Relevance
“…The classical nucleation theory has been widely used to correlate experimental measurements. 4,5 It has been shown that the theory generally predicts the supersaturation dependence of the nucleation rate quite well but not the temperature dependence. To develop a better theory, either phenomenological or molecular, of nucleation, it would be desirable to obtain the formation free energy ͑i.e., barrier of nucleation͒ for a commonly studied model system, such as the Lennard-Jones ͑12,6͒ fluid, from first principles.…”
Section: Introductionmentioning
confidence: 99%
“…The classical nucleation theory has been widely used to correlate experimental measurements. 4,5 It has been shown that the theory generally predicts the supersaturation dependence of the nucleation rate quite well but not the temperature dependence. To develop a better theory, either phenomenological or molecular, of nucleation, it would be desirable to obtain the formation free energy ͑i.e., barrier of nucleation͒ for a commonly studied model system, such as the Lennard-Jones ͑12,6͒ fluid, from first principles.…”
Section: Introductionmentioning
confidence: 99%
“…From the nucleation theorem 9 it would then follow that one of the two components has a negative concentration in the critical nucleus. Laaksonen and Oxtoby, who used density functional theory to study nucleation in a mixture, 10,11 argue that the failure of CNT can be traced back to the fact that this theory does not predict the composition of the critical nucleus correctly.…”
Section: Introductionmentioning
confidence: 99%
“…As the parameter a increases, the MOFA of positive and negative ions approach each other. Note that neutral A a W w clusters which are also important in theories of homogeneous bi-molecular nucleation have so far not been measured (Laaksonen et al 1995;Kulmala et al 2004). Therefore the cluster ion measurements also help to constrain theories on homogeneous nucleation.…”
Section: Ion Induced Sulphuric Acid Nucleationmentioning
confidence: 99%